Exploring Gifted Education Program and Practice in Rural Appalachia - Miller, Myriah; Brigandi, Carla (Theory & Practice in Rural Education, 2020)
The literature on rural gifted programs is growing, but understandings of programmatic features and the teachers within the gifted programs in rural Appalachia are still largely underdeveloped. Through an exploratory case study of three rural Appalachian gifted programs, this study provides a glimpse into their organizational structures and the teachers’ experiences and perceptions. The illustrative findings indicate that teachers utilized their resources and knowledge to manufacture their gifted curricula and expressed competing narratives of place and globality. Also, misassumptions and unsupported practices in this rural place negatively influenced teacher retention. Implications and future steps are addressed.